Investment Motivations and UK Business Angels' Appetite for Risk Taking: The Moderating Role of Experience. (13th August 2019) - Croce, Annalisa; Ughetto, Elisa; Cowling, Marc
Abstract: In this paper we use a large UK survey of business angels (BAs) investing in two different publicly supported schemes to directly question the role that investment motivations play in shaping investors' appetite for risk. We dive deeper into the relationship between investment reasons and risk taking, by exploring the potential for a moderating effect derived from BAs' past experience (i.e. financial and entrepreneurial experience). Our analysis reveals that both investment reasons (for return and for passion) have substantial explanatory power in shaping angels' risk attitude, but their effect is moderated by the investors' prior experience. This key finding represents important empirical support for what has so far been anecdotal evidence concerning BAs' appetite for risk when investing.